Bio-Inspired Synthesis of Carbon-Based Nanomaterials and Their Potential Environmental Applications: A State-of-the-Art Review - Vishal Dutta; Ritesh Verma; C. Gopalkrishnan; Min-Hao Yuan; Khalid Mujasam Batoo; R. Jayavel; Ankush Chauhan; Kun-Yi Andrew Lin; Ravindran Balasubramani; Suresh Ghotekar (Inorganics, 2022)
Providing safe drinking water and clean water is becoming a more challenging task all around the world. Although some critical issues and limits remain unsolved, implementing ecologically sustainable nanomaterials (NMs) with unique features, e.g., highly efficient and selective, earth-abundance, renewability, low-cost manufacturing procedures, and stability, has become a priority. Carbon nanoparticles (NPs) offer tremendous promise in the sectors of energy and the environment. However, a series of far more ecologically friendly synthesis techniques based on natural, renewable, and less expensive waste resources must be explored. This will reduce greenhouse gas emissions and harmful material extraction and assist the development of green technologies. The progress achieved in the previous 10 years in the fabrication of novel carbon-based NMs utilizing waste materials as well as natural precursors is reviewed in this article. Research on carbon-based NPs and their production using naturally occurring precursors and waste materials focuses on this review research. Water treatment and purification using carbon NMs, notably for industrial and pharmaceutical wastes, has shown significant potential. Research in this area focuses on enhanced carbonaceous NMs, methods, and novel nano-sorbents for wastewater, drinking water, groundwater treatment, as well as ionic metal removal from aqueous environments. Discussed are the latest developments and challenges in environmentally friendly carbon and graphene quantum dot NMs.